C-NAR: Best Practice Tindakan Pembimbingan Berkelanjutan PPL PPG Prajabatan Universitas Negeri Medan - Faisal Faisal (Universitas Negeri Padang, 2021)
AbstractThis study aims to describe the implementation of the continuous mentoring process as an effort to produce students, Field Supervisors (DPL), and Civil Service Teachers (GP) who are reflective in the implementation of PPL PPG Prajabatan at UNIMED. The type of research used is Collaborative Nested Action Research (C-NAR). In its implementation, in addition to guiding and being directly involved in Class Action Research (PTK) conducted by students, DPL and GP also conduct Guidance Action Research (PTB) to find the best sustainable ways or innovations in carrying out mentoring. The results showed that through the C-NAR, students, DPL, and GP PPG Prajabatan have succeeded in carrying out various continuous improvements in mentoring, among others. (1) exemplifying interactive learning patterns by GP virtually even though they are not from partner schools, (2) developing supplementary learning tools in the form of interactive teaching materials, interactive media, interactive worksheets, and interactive quizzes as interactive learning resources for students, and (3 ) facilitate parents with guidebooks for using supplementary teaching materials so that they are helpful in guiding students to study at home.